IMPLEMENTASI MANAGEMENT NETWORK SECURITY PADA LABORATORIUM CISCO UNIVERSITAS BINA DARMA - Negara , Edi Surya (Universitas Bina Darma, 2014)
The development of computer network technology as a medium for data communications to this increase. The need for the use of shared resources on the network both software and hardware has resulted in the emergence of a variety of network technology development itself. Along with the high level of need and the increasing number of network users who want some form of network that can deliver maximum results, in terms of both efficiency and increase network security itself, the improvement efforts continue to be made by the various parties. One measure of the quality of the computer network management and network security is good. By it because they needed a real action to create a system management and network security is good. So with the management and security of the network that will either guide to good computer network.